Living with art - Getlein, Mark. (McGraw-Hill, 2013)
Living with art's approach to art appreciation supports student's acquisition of the essential skills of the course... It's provides the foundation for a lifelong appriciation of art, and critical-thingking skills that will benefit students for beyond the classroom into their chosen careers.